Penerapan Analisisi SWOT Dalam Manajemen Kurikulum Dan Pembelajaran Di SMK Putra Anda Binjai - Rahmad Rinaldi (Cybernetics: Journal Educational Research and Social Studies, 2021)
The quality mechanism in the education unit must be able to be implemented properly, so that the education unit always presents the best quality and strives to continuously improve the quality of what it has achieved. Quality is a measure for customers and users of education, namely parents, government and private agencies who will use the services of an education. Education is said to be of quality if there is a balance between input, process and output. Achievements with the application of SWOT Analysis based on logic that can maximize strengths and opportunities, so as to minimize weaknesses and threats at the same time. The results of writing about the application of SWOT analysis in curriculum management and learning at SMK Putra Anda Binjai are aimed at; 1) So that schools are able to detect and measure strengths, weaknesses, opportunities and threats, in order to follow up on the right strategy in improving the quality of curriculum and learning, 2) The process of applying SWOT analysis in Curriculum Management and Learning at SMK Putra Anda Binjai.